Estudio de adsorción de antimonio en soluciones sintéticas utilizando perlas de quitosano modificado con hierro chifer - Pardo Loaiza, Carlos Luis (2017)
The presence of heavy metals in the hydrological cycle, potentially toxic elements, is due to the action of man. Industrial activity contaminates this environment up to 100 - 1000 times more than these metals that are naturally found in the Earth's crust. Contamination of water by heavy metals is an important environmental threat to living beings, as they are toxic in small and large doses. Due to the difficulty to remove small concentrations of heavy metals in the water and the generation of a great environmental impact, this degree project has been based on the scientific investigation and application of the same in the aqueous medium, of a non conventional technique of heavy metals adsorption by natural agricultural and industrial materials; Focusing primarily on antimony, which turns out to be harmful to the health of living beings, causing various diseases and even death. Although initially used to treat diseases such as leishmaniasis, schistosomiasis, ascariasis, trypanosomes and bilharziasis, over time and research conducted, antimony was ruled out as an element of medication. The cell walls of the adsorbent materials contain polysaccharides, proteins, lipids and large functional groups capable of binding heavy metals on their surface. For this, chitosan modified with iron was used, it is obtained by the deacetylation of chitin, which is also obtained from the exoskeletons of crustaceans such as shrimp and crab, discarded from the industries. The use of chitosan has received great attention in the application for the adsorption of metallic ions because it is a low cost, abundant and available in nature adsorbent. Readily, chitosan can be chemically or physically modified to obtain derivatives through different processes that may be employed to improve the adsorption kinetics of metal ions. Chitosan is physically modified by the preparation of the polymer in several forms, to be an adsorbent material, it mainly depends on the porosity, surface area and particle size. The chemical modifications of chitosan generate new and improved properties in the polymer, thus improving the adsorption properties and preventing the polymer dissolution in acidic solutions. It offers a myriad of possibilities, such as reticulation and grafting reactions of molecules. When tested with different concentrations of chitosan in aqueous solutions; and, when modifying the pH of the same to find the most optimum, which achieves greater adsorption, it was concluded that pH 6 is the best at the time of using iron-modified chitosan as an antimony adsorbent. In this way, the adsorption isotherm is achieved, where the results are adjusted to the Langmuir model due to an homogeneous surface and when all the sites are occupied, it is no longer possible to continue the adsorption, that is, the system becomes saturated. And, in the kinetics of adsorption, at first there is an adsorption of antimony at high speed, but with the passage of time it decreases and reaches equilibrium.